Virtuality and Development: Philosophical, Aesthetic, Psychological and Pedagogical aspects - Bús Imre (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2018)
Abstract. Computers and the applications of today’s high technology can simulate reality so realistically that virtuality has become part of both children’s and adults’ lifestyles. However, it did not emerge with the computer applications, but with human thinking and part of that, the virtual conception of the world. This development can be observed on individuals, as well. Virtuality has an important role in the transition from babyhood into adult life, the elements of which can be described from different aspects. This study shows the development of virtuality through the examples of cultural, philosophical, aesthetic, then the psychological and pedagogical development of the individual with the help of some important studies.

A technológiai fejlődés mai fokán a számítógépek, illetve azok programjai már annyira élethűen szimulálják a valóságot, hogy a virtualitás a gyermekek és a felnőttek életmódjának is a része lett. Ez azonban nem a számítógépes alkalmazásokkal jött létre, hanem az emberi gondolkodással, és annak részeként a világ virtuális felfogásával. Ennek egyénekre vonatkozó fejlődési vonala is kimutatható. A csecsemőből felnőtt emberré történő átalakulásában jelentős szerepe van a virtualitásnak, amelynek elemei jól leírhatók különböző nézőpontokból. A tanulmány a társadalmi fejlődés jellemző kulturális, filozófiai, esztétikai, majd az egyéni fejlődés pszichológiai és pedagógiai példáin keresztül mutatja be a virtualitás fejlődését néhány fontos munka segítségével.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2018_tom-v_v-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008404
Keywords: virtuality; reality; play; ontogeny and fantasy development